HIV/AIDS Awareness among VCT Clients: A Cross-Sectional Study from Delhi, India. (4th June 2014) - Mehra, Bhanu; Bhattar, Sonali; Bhalla, Preena; Rawat, Deepti
Abstract : The contribution of India to the global burden of HIV/AIDS is significant. A major barrier that the country has faced in its battle against this disease is the inadequate and inaccurate information about it among the population. The present analysis explores the knowledge about HIV/AIDS among clients attending a voluntary counselling and testing (VCT) facility in India. Two hundred clients attending the VCT facility were assessed in this regard using a structured predesigned questionnaire. Sixty-three (31.5%) of the respondents had never heard of HIV/AIDS. In comparison to males, a significantly higher number of females had not heard about the disease (P < 0.01 ). Lower levels of education of participants were found to be significantly associated with the response of not having heard of HIV/AIDS (P < 0.01 ) as was an occupation status of being an unemployed man/housewife (P = 0.002 ). For the 137 (68.5%) respondents who had heard about HIV/AIDS, television was the source of information in 130 (94.9%) followed by posters in 93 (67.9%) and newspapers in 88 (64.2%). While the knowledge about HIV transmission and prevention was good, the extent of misconceptions was high (61.8%). Our study highlights the strong need to raise the levels of HIV awareness among Indian population.